2016
DOI: 10.1016/j.pbb.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent methylphenidate treatment differentially alters adult impulsivity and hyperactivity in the Spontaneously Hypertensive Rat model of ADHD

Abstract: Impulsivity and hyperactivity are two facets of attention deficit/hyperactivity disorder (ADHD). Impulsivity is expressed as reduced response inhibition capacity, an executive control mechanism that prevents premature execution of an intermittently reinforced behavior. During methylphenidate treatment, impulsivity and hyperactivity are decreased in adolescents with ADHD, but there is little information concerning levels of impulsivity and hyperactivity in adulthood after adolescent methylphenidate treatment is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 113 publications
3
25
1
Order By: Relevance
“…Indeed, we found that WKY display less open field activity than SHR and WIS (Somkuwar et al 2016). However, in the current work assessing cocaine abuse vulnerability, VEH-treated WKY and WIS did not significantly differ on any measure of cocaine self-administration, with the exception of differences in cocaine intake at the post-acquisition time point and at the 0.1 mg/kg cocaine dose under the FR1 schedule.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Indeed, we found that WKY display less open field activity than SHR and WIS (Somkuwar et al 2016). However, in the current work assessing cocaine abuse vulnerability, VEH-treated WKY and WIS did not significantly differ on any measure of cocaine self-administration, with the exception of differences in cocaine intake at the post-acquisition time point and at the 0.1 mg/kg cocaine dose under the FR1 schedule.…”
Section: Discussionmentioning
confidence: 72%
“…SHR exhibit core behavioral and cognitive symptoms of ADHD, including hyperactivity, impulsivity, and inattention (Adriani et al 2003; Bayless et al 2015; Hill et al 2012; Sagvolden et al 2000; Somkuwar et al 2016). SHR also model neurobiological abnormalities observed in ADHD, including greater striatal dopamine transporter density (Roessner et al 2010; Silva et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to controls, SHR are more hyperactive (Sagvolden et al, 1992), inattentive (Jentsch, 2005; De Bruin et al, 2003), and impulsive (Hand et al, 2009; Somkuwar et al, 2016). SHR also have impaired working memory (Nakamura-Palacios et al, 1996; De Bruin et al, 2003; Kantak et al, 2008) and show behavioral flexibility and habit learning deficits (Kantak et al, 2008; Wells et al, 2010; Harvey et al, 2013; Gauthier et al, 2014; Jordan et al, 2016).…”
mentioning
confidence: 93%
“…In addition, SHR were more reactive to cocaine-paired cues and took longer to extinguish cocaine-seeking responses than WKY and WIS (Jordan et al, 2014; Jordan et al, 2016). Moreover, SHR had heightened locomotor activity, cocaine sensitization, and impulsive action compared to WKY and WIS (Somkuwar et al, 2016). …”
mentioning
confidence: 99%
“…We used the inbred Spontaneously Hypertensive Rat (SHR) model of ADHD because this strain displays core characteristics of ADHD. Compared to controls, SHR are more hyperactive, inattentive, and impulsive (Sagvolden et al 1992; Jentsch 2005; De Bruin et al 2003; Hand et al 2009; Somkuwar et al 2016). SHR also have impaired working memory and show deficits in behavioral flexibility and habit learning (Nakamura-Palacios et al 1996; De Bruin et al 2003; Kantak et al 2008; Wells et al 2010; Harvey et al 2013; Gauthier et al 2014; Jordan et al 2016b).…”
Section: Introductionmentioning
confidence: 92%